Relationship between baseline D-dimer and prognosis in Japanese patients with venous thromboembolism: Insights from the J’xactly study - Migita, Shohei; Okumura, Yasuo; Fukuda, Ikuo; Nakamura, Mashio; Yamada, Norikazu; Takayama, Morimasa; Maeda, Hideaki; Yamashita, Takeshi; Ikeda, Takanori; Mo, Makoto; Yamazaki, Tsutomu; Hirayama, Atsushi (Frontiers in Cardiovascular Medicine, 2023)
Background D-dimer is a biomarker of fibrin production and degradation, and changes in D-dimer concentration suggest fibrin clot formation, which is associated with thromboembolism and hypercoagulable states. Thus, an elevated D-dimer concentration could be a useful prognostic predictor for patients with venous thromboembolism (VTE). Methods and results In this subanalysis of the J’xactly study, a prospective multicenter study conducted in Japan, we examined the clinical outcomes of 949 patients with VTE stratified by baseline D-dimer concentration. The median D-dimer concentration was 7.6 μg/ml (low D-dimer group: <7.6 μg/ml [n = 473, 49.8%]; high D-dimer group: ≥7.6 μg/ml [n = 476, 50.2%]). The mean age of the patients was 68 years, and 386 patients (40.7%) were male. Compared with the low D-dimer group, the high D-dimer group had more frequent pulmonary embolism with or without deep vein thrombosis (DVT), proximal DVT, atrial fibrillation, or diabetes mellitus, and underwent intensive treatment with 30 mg/day rivaroxaban. The incidence of composite clinically relevant events (recurrence or exacerbation of symptomatic VTE, acute coronary syndrome [ACS], ischemic stroke, death from any cause, or major bleeding) was higher in the high D-dimer group than in the low D-dimer group (11.1% vs. 7.5% per patient-year; hazard ratio, 1.46; 95% confidence interval, 1.05–2.04; p = 0.025). There was no significant difference between the high and low D-dimer groups in the incidence of VTE (2.8% vs. 2.5% per patient-year, respectively; p = 0.788), ACS (0.4% per patient-year vs. not observed, respectively; p = 0.078), or major bleeding (4.0% vs. 2.1% per patient-year, respectively; p = 0.087), but there was a significant difference in the incidence of ischemic stroke (1.0% per patient-year vs. not observed, respectively; p = 0.004). Conclusion Elevated D-dimer concentration may be an important prognostic predictor in Japanese patients with VTE. Clinical Trial Registration: UMIN CTR, UMIN000025072 (https://www.umin.ac.jp/ctr/index.htm).